Can vitamin D levels affect your risk of melanoma?. (2nd January 2020) - Liyanage, U.E.; Law, M.H.; ,; Barrett, J.H.; Iles, M.M.; MacGregor, S.
Summary: Melanoma, the most lethal form of skin cancer. According to Australian cancer database statistics, the incidence (meaning number of cases) of melanoma in 2018 was 14, 778 and the number of deaths was 1, 684. There is considerable debate in the medical literature (e.g. journals) on the role that vitamin D may play in melanoma risk. Some studies link vitamin D deficiency, meaning lower levels of vitamin D, with an increased risk of a range of different cancers. Studies into melanoma are fraught with difficulties because while higher ultraviolet radiation levels (UVR) from the sun increase the body's vitamin D levels, UVR exposure can also increase the risk of melanoma. In this project, the authors aimed to determine if vitamin D levels can affect melanoma risk. They performed Mendelian randomization (MR), a way of analysing different variants of genes that can be used to determine causality (cause and effect). The study used European ancestry genetic data, together with data linking genetic markers to vitamin D levels. The authors showed that even large predicted changes in vitamin D levels (a 20 nmol/L decrease), only negligibly affected melanoma risk. Whilst some studies have suggested that modifying vitamin D levels may reduce melanoma risk, this study provides no evidence that genetically determined vitamin D is causally associated (linked) with melanoma risk. This summary relates to the study: Is there a causal relationship between vitamin D and melanoma risk? A Mendelian randomization study Abstract : Linked Article:  Liyanage et al. Br J Dermatol 2020; 182 :97–103